Epicuticular chemistry reinforces the new taxonomic classification of the Bactrocera dorsalis species complex (Diptera: Tephritidae, Dacinae) - Vaníčková, Lucie; Nagy, Radka; Pompeiano, Antonio; Kalinová, Blanka (PloS one, 2017)
Bactrocera invadens Drew, Tsuruta & White, Bactrocera papayae Drew & Hancock, and Bactrocera philippinensis Drew & Hancock, key pest species within the Bactrocera dorsalis species complex, have been recently synonymized under the name Bactrocera dorsalis (Hendel). The closely related Bactrocera carambolae Drew & Hancock remains as a discrete taxonomic entity. Although the synonymizations have been accepted by most researchers, debate about the species limits remains. Because of the economic importance of this group of taxa, any new information available to support or deny the synonymizations is valuable. We investigated the chemical epicuticle composition of males and females of B. dorsalis, B. invadens, B. papayae, B. philippinensis, and B. carambolae by means of one- and two-dimensional gas chromatography-mass spectrometry, followed by multiple factor analyses and principal component analysis. Clear segregation of complex cuticule profiles of both B. carambolae sexes from B. dorsalis (Hendel) was observed. In addition to cuticular hydrocarbons, abundant complex mixtures of sex-specific oxygenated lipids (three fatty acids and 22 fatty acid esters) with so far unknown function were identified in epicuticle extracts from females of all species. The data obtained supports both taxonomic synonymization of B. invadens, B. papayae, and B. philippinensis with B. dorsalis, as well as the exclusion of B. carambolae from B. dorsalis.
Keywords: Gas Chromatography-Mass Spectrometry; Factor Analysis, Statistical; druhová specificita; plynová chromatografie s hmotnostně spektrometrickou detekcí; kožní systém; Integumentary System; Animals; Hydrocarbons; Tephritidae; uhlovodíky; zvířata; Species Specificity; faktorová analýza statistická